Magnetism of Molecular Conductors - Manuel Almeida (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The study of the magnetic properties of molecular conductors has experienced, over the last few decades, a very significant evolution, comprising systems of increasing molecular complexity and moving towards multifunctional materials. In this context, molecular magnetic conductors have emerged at the intersection between the fields of molecule-based conductors and molecule-based magnets as a very exciting class of multifunctional materials in which the interaction and synergy between conduction electrons and localized magnetic moments can lead to new phenomena, complex phase diagrams, and different ground states, with a large potential for technological applications, namely in electronic devices, sensors and spintronics. Among these phenomena are unusual field-induced transitions, including magnetic-field-induced superconductivity, very large magnetoresistance effects, conductors that are switchable by magnetic field, changes of magnetic ordering or spin state, etc. This Special Issue of Magnetochemistry features a collection of research contributions illustrating recent achievements on different aspects of the development, study and understanding of the magnetic properties of molecular conductors and their applications. Many different types of compounds are considered in this Special Issue.